Critical mineral resources – lithium (Li) - Đedović - Handanović, Dubravka (Napredak, 2024)
This paper analyzes the concepts and methodologies used by the USA and the EU for establishing the list of critical raw materials (CRM). Critical raw materials as key elements for national security and economy play an important role in energy, industrial and military technologies. The USA has adopted the methodology based on economic vulnerability, disruption potential, trade exposure and supply risk, while the EU uses the criteria of economic importance and supply risk. The CRM lists in the USA and the EU are regularly updated so that the USA included 50 raw materials in its 2023 list, while the EU has 34 raw materials in its list. This paper also considers the importance of lithium as one of the key raw materials at the global level and gives a review of large lithium producers and suppliers, as well as Serbia’s potential in this field. Lithium is particularly important for the production of batteries, electronics and space technologies.